Fire safety in space – Investigating flame spread interaction over wires - Citerne, Jean-Marie; Dutilleul, Hugo; Kizawa, Koki; Nagachi, Masashi; Fujita, Osamu; Kikuchi, Masao; Jomaas, Grunde; Rouvreau, Sébastien; Torero, Jose L.; Legros, Guillaume (Acta astronautica, 2016)
A new rig for microgravity experiments was used for the study flame spread of parallel polyethylene-coated wires in concurrent and opposed airflow. The parabolic flight experiments were conducted at small length- and time scales, i.e. typically over 10cm long samples for up to 20s. For the first time, the influence of neighboring spread on the mass burning rate was assessed in microgravity. The observations are contrasted with the influence characterized in normal gravity. The experimental results are expected to deliver meaningful guidelines for future, planned experiments at a larger scale. Arising from the current results, the issue of the potential interaction among spreading flames also needs to be carefully investigated as this interaction plays a major role in realistic fire scenarios, and therefore on the design of the strategies that would allow the control of such a fire. Once buoyancy has been removed, the characteristic length and time scales of the different modes of heat and mass transfer are modified. For this reason, interaction among spreading flames may be revealed in microgravity, while it would not at normal gravity, or vice versa. Furthermore, the interaction may lead to an enhanced spread rate when mutual preheating dominates or, conversely, a reduced spread rate when oxidizer flow vitiation is predominant. In more general terms, the current study supports both the SAFFIRE and the FLARE projects, which are large projects with international scientific teams. First, material samples will be tested in a series of flight experiments (SAFFIRE 1-3) conducted in Cygnus vehicles after they have undocked from the ISS. These experiments will allow the study of ignition and possible flame spread in real spacecraft conditions, i.e. over real length scale samples within real time scales. Second, concomitant research conducted within the FLARE project is dedicated to the assessment of new standard tests for materials that a spacecraft can be composed of. Finally, these tests aim to define the ambient conditions that will mitigate and potentially prohibit the flame spread in microgravity over the material studied.